The Sidelined Front-liners: Eritrean CBOs in Greater Cairo - Hegazy, Nada (AUC Knowledge Fountain, 2023)
Despite the recognition of the important role that community-based organizations play, among international actors concerned with refugee issues, as well as UNHCR’s adoption of a community-based approach to protection; community-based organizations continue to be sidelined by these actors. This thesis explores the role that Eritrean CBOs play in improving the lives of Eritrean refugees and asylum-seekers living in Greater Cairo. It also investigates the challenges that they face while trying to operate in Egypt. Using a multi-scalar lens, the research examines the relationships between Eritrean CBOs and Eritrean refugees and asylum-seekers, the State, UNHCR and its partner organizations, in addition to their relationship with one another. Through the narratives of nine Eritrean CBOs, two partner organizations, and six focus group discussions with Eritrean refugees, asylum-seekers, and closed-file refugees, this thesis shows that Eritrean CBOs play a significant role in improving the socio-economic conditions of Eritrean refugees and asylum-seekers. However, they are sidelined by the formal refugee-serving organizations in Egypt. It also argues that while their marginality allows them to function without having to bear the cost of the mainstream, it also causes them to face significant challenges with regards to funding and sustainability. The findings of the thesis suggest that Eritrean CBOs are not viewed as partners by formal refugee-concerned actors, despite being the front-liners and the first respondents to their community’s needs.